Question
upstudy study bank question image url

b) Using Lagrange's formula for interpolation find the value of \( y \) when \( x=2 \) from the ( \( ) \) following table \[ \begin{array}{lrrrr} x: & -2 & -1 & 0 & 4 \\ y: & -2 & 4 & 1 & 8 \end{array} \]

Ask by Hammond Hilton. in India
Jan 01,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

The value of \( y \) when \( x = 2 \) is \( -10.2 \).

Solution

Sign in to Unlock Answers for Free!

A Learning Platform Trusted by Millions of Real Students and Teachers.

star-icon Unlock

Answered by UpStudy AI and reviewed by a Professional Tutor

The Deep Dive

To find the value of \( y \) when \( x = 2 \) using Lagrange's interpolation formula, we start with the given points: \((-2, -2)\), \((-1, 4)\), \((0, 1)\), and \((4, 8)\). The formula is given by: \[ P(x) = \sum_{i=0}^{n} y_i L_i(x) \] where \(L_i(x)\) is the Lagrange basis polynomial defined as: \[ L_i(x) = \prod_{j=0, j \neq i}^{n} \frac{x - x_j}{x_i - x_j} \] For our interpolation, we have \(n = 3\) (since there are 4 points). Let's calculate: 1. **For \(L_0(x)\)** (\(y = -2\) when \(x = -2\)): \[ L_0(x) = \frac{(x + 1)(x)(x - 4)}{(-2 + 1)(-2 - 0)(-2 - 4)} = \frac{(x + 1)x(x - 4)}{(-1)(-2)(-6)} = -\frac{(x + 1)x(x - 4)}{12} \] 2. **For \(L_1(x)\)** (\(y = 4\) when \(x = -1\)): \[ L_1(x) = \frac{(x + 2)(x)(x - 4)}{(-1 + 2)(-1 - 0)(-1 - 4)} = \frac{(x + 2)x(x - 4)}{(1)(-1)(-5)} = \frac{(x + 2)x(x - 4)}{5} \] 3. **For \(L_2(x)\)** (\(y = 1\) when \(x = 0\)): \[ L_2(x) = \frac{(x + 2)(x + 1)(x - 4)}{(0 + 2)(0 + 1)(0 - 4)} = \frac{(x + 2)(x + 1)(x - 4)}{(2)(1)(-4)} = -\frac{(x + 2)(x + 1)(x - 4)}{8} \] 4. **For \(L_3(x)\)** (\(y = 8\) when \(x = 4\)): \[ L_3(x) = \frac{(x + 2)(x + 1)(x)}{(4 + 2)(4 + 1)(4 - 0)} = \frac{(x + 2)(x + 1)(x)}{(6)(5)(4)} = \frac{(x + 2)(x + 1)(x)}{120} \] Now, plug \(x = 2\) into the Lagrange polynomial: \[ P(2) = (-2) L_0(2) + 4 L_1(2) + 1 L_2(2) + 8 L_3(2) \] Calculating each \(L\): - \(L_0(2) = -\frac{(2 + 1)(2)(2 - 4)}{12} = -\frac{3 \cdot 2 \cdot (-2)}{12} = 1\) - \(L_1(2) = \frac{(2 + 2)(2)(2 - 4)}{5} = \frac{4 \cdot 2 \cdot (-2)}{5} = -\frac{16}{5}\) - \(L_2(2) = -\frac{(2 + 2)(2 + 1)(2 - 4)}{8} = -\frac{4 \cdot 3 \cdot (-2)}{8} = 3\) - \(L_3(2) = \frac{(2 + 2)(2 + 1)(2)}{120} = \frac{4 \cdot 3 \cdot 2}{120} = \frac{24}{120} = \frac{1}{5}\) Substituting back: \[ P(2) = (-2)(1) + 4(-\frac{16}{5}) + 1(3) + 8(\frac{1}{5}) \] \[ = -2 - \frac{

Related Questions

Latest Pre Calculus Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy